On religious diversity - McKim, Robert (Oxford University Press, 2012)
Robert McKim's goal in 'On Religious Diversity' is to distinguish and examine a number of possible responses to the knowledge of other religious traditions that are available to all of us today. He argues that the issues raised will be of pressing importance throughout the century we have just begun.